Studi keterlibatan perempuan dalam lembaga legislatif dalam indeks pembangunan gender di Provinsi Jawa Barat - Abidin, Ali Zainal; Arif, Muhammad; Abroroh, Sittah Alifia (Journal of Economics Research and Policy Studies, 2022)
The research was carried out to investigate women's contributions in the political aspect, especially in the legislative institutions in the province of West Java, Indonesia. This study uses a quantitative approach, with data processing based on panel data analysis. The Gender Development Index (IPG) was chosen as the dependent variable. In contrast, the independent variables used the Total Female Population (JPP), Average Years of Schooling (RLS), Number of Female Legislative Members (JALP), and the Gender Empowerment Index (IBG). The study used the province of West Java as the location, with secondary data from 2017 to 2020. The results showed that the average length of schooling (RLS) was the only variable positively influencing the Gender Development Index (GPA). This shows that the contribution of women on the political stage will increase along with the number of women with higher education. Other variables do not affect the index.